Indy dreams and urban nightmares: speed merchants, spectacle, and the struggle over public space in the world-class city - Lowes, Mark Douglas, 1969- (Indy Dreams and Urban Nightmares., 2002)
Lowes examines the conflict that arose between a Vancouver community and the civic boosters who wanted to move the Molson Indy Vancouver motorsport event to their neighbourhood park.